Students Vocabulary Mastery toward Crossword Puzzle Games - Rahmat Nasrullah; Nur Rizky Alfiany; Muhammad Ainul Hamdan (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2021)
This research investigated the improvement of students’ participation and vocabulary achievement by using crossword puzzles in the classroom. The research design was Classroom Action Research (CAR) conducted in two cycles. The research subjects were the seventh-grade students and the research area was at a private Islamic Junior High School in Kendari. The data were collected by using observation and vocabulary achievement tests. The collected data were analyzed statistically by using a percentage formula. The students’ activity improved from 78,66% in cycle 1 to 97,66% in cycle 2. Meanwhile, the students’ vocabulary mastery improved from 54% in cycle 1 to 90% in cycle 2. In conclusion, using crossword puzzles improved the students’ vocabulary achievement and students' participation in the teaching and learning English.